The JAK inhibitor tofacitinib suppresses synovial JAK1-STAT signalling in rheumatoid arthritis. Issue 6 (14th November 2014) - Boyle, D L; Soma, K; Hodge, J; Kavanaugh, A; Mandel, D; Mease, P; Shurmur, R; Singhal, A K; Wei, N; Rosengren, S; Kaplan, I; Krishnaswami, S; et al.
Abstract : Objective: Tofacitinib is an oral Janus kinase (JAK) inhibitor for the treatment of rheumatoid arthritis (RA). The pathways affected by tofacitinib and the effects on gene expression in situ are unknown. Therefore, tofacitinib effects on synovial pathobiology were investigated. Methods: A randomised, double-blind, phase II serial synovial biopsy study (A3921073; NCT00976599 ) in patients with RA with an inadequate methotrexate response. Patients on background methotrexate received tofacitinib 10 mg twice daily or placebo for 28 days. Synovial biopsies were performed on Days -7 and 28 and analysed by immunoassay or quantitative PCR. Clinical response was determined by disease activity score and European League Against Rheumatism (EULAR) response on Day 28 in A3921073, and at Month 3 in a long-term extension study (A3921024; NCT00413699 ). Results: Tofacitinib exposure led to EULAR moderate to good responses (11/14 patients), while placebo was ineffective (1/14 patients) on Day 28. Tofacitinib treatment significantly reduced synovial mRNA expression of matrix metalloproteinase (MMP)-1 and MMP-3 (p<0.05) and chemokines CCL2, CXCL10 and CXCL13 (p<0.05). No overall changes were observed in synovial inflammation score or the presence of T cells, B cells or macrophages. Changes in synovial phosphorylation of signal transducer and activator of transcription 1 (STAT1) and STAT3 strongly correlated with 4-month clinical responses (p<0.002). Tofacitinib significantly decreased plasma CXCL10 (p<0.005) at Day 28 compared with placebo. Conclusions: Tofacitinib reduces metalloproteinase and interferon-regulated gene expression in rheumatoid synovium, and clinical improvement correlates with reductions in STAT1 and STAT3 phosphorylation. JAK1-mediated interferon and interleukin-6 signalling likely play a key role in the synovial response. Trial registration number: NCT00976599.